Family history of mood disorder and characteristics of major depressive disorder : A STARD (sequenced treatment alternatives to relieve depression) study - NIERENBERG, Andrew A; TRIVEDI, Madhukar H; FAVA, Maurizio; BIGGS, Melanie M; SHORES-WILSON, Kathy; WISNIEWSKI, Stephen R; BALASUBRAMANI, G. K; RUSH, A. John (Journal of psychiatric research, 2007)
Clinicians routinely ask patients with major depressive disorder (MDD) about their family history. It is unknown, however, if patients who report a positive family history differ from those who do not. This study compared the demographic and clinical features of a large cohort of treatment-seeking outpatients with non-psychotic MDD who reported that they did or did not have at least one first-degree relative who had either MDD or bipolar disorder. Subjects were recruited for the STAR( *)D multicenter trial. Differences in demographic and clinical features for patients with and without a family history of mood disorders were assessed after correcting for age, sex, race, and ethnicity. Patients with a family history of mood disorder (n=2265; 56.5%) were more frequently women and had an earlier age of onset of depression, as compared to those without such a history (n=1740; 43.5%). No meaningful differences were found in depressive symptoms, severity, recurrence, depressive subtype, or daily function. Women were twice as likely as men to report a positive family history of mood disorder, and a positive family history was associated with younger age of onset of MDD in the proband. Consistent with prior research, early age of onset appears to define a familial and, by extension, genetic subtype of major depressive disorder.